2023
DOI: 10.1007/s00253-023-12441-3
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic factors and endophytes co-regulate flavone and terpenoid glycoside metabolism in Glycyrrhiza uralensis

Abstract: Recently, endorhizospheric microbiota is realized to be able to promote the secondary metabolism in medicinal plants, but the detailed metabolic regulation metabolisms and whether the promotion is influenced by environmental factors are unclear yet. Here, the major flavonoids and endophytic bacterial communities in various Glycyrrhiza uralensis Fisch. roots collected from seven distinct places in northwest China, as well as the edaphic conditions, were characterized and analyzed. It was found that the soil moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…To protect against damage from biotic and abiotic stresses, the plant synthesizes flavonoids that act as antitoxins or antioxidants [23]. Endophytic fungus (Rhizobium rhizolycopersici GUH21) has been shown to significantly enhance the accumulation of isoglycyrrhizin and glycyrrhetinic acid in the root system of Glycyrrhiza glabra under increased watering and low temperatures [24].…”
Section: Discussionmentioning
confidence: 99%
“…To protect against damage from biotic and abiotic stresses, the plant synthesizes flavonoids that act as antitoxins or antioxidants [23]. Endophytic fungus (Rhizobium rhizolycopersici GUH21) has been shown to significantly enhance the accumulation of isoglycyrrhizin and glycyrrhetinic acid in the root system of Glycyrrhiza glabra under increased watering and low temperatures [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, their different effects on the physiological growth of G. uralensis were not well studied and still cannot be applied to G. uralensis production. Moreover, it was reported that inoculation of endophytic fungi in G. uralensis could improve its active ingredient content, but this technique remains in the laboratory research stage and cannot yet be stably applied to G. uralensis cultivation (Mohamad et al, 2018;Liu et al, 2023). Therefore, it is essential to seek effective measures to regulate the quality of G. uralensis during its cultivation management.…”
Section: Introductionmentioning
confidence: 99%